Intracellular growth and drug susceptibility of Mycobacterium tuberculosis in macrophages - Sakarin Chanwong (2018)
Intracellular growth of Mycobacterium tuberculosis in human and rabbit monocytes and in mouse and guinea pig macrophages was evaluated. Monocytes or macrophages were infected with M. tuberculosis H37Rv with the multiplicity of infection at 10 mycobacteria per monocyte. The average percentages of infected human and rabbit monocytes were 22% and 19%, while mouse and guinea pig macrophages were 46% and 58%, respectively. The average generation times of M. tuberculosis H37Rv inside human and rabbit monocytes and in mouse and guinea pig macrophages, after culturing the infected cells for 10 days, were 33.4, 50.3, 31.4, and 25.6 h, respectively. Using infected guinea pig macrophages for intracellular evaluation of drug susceptibility, the minimal inhibitory concentrations (MICs) of isoniazid to the intracellular and extracellular M. tuberculosis H37Rv were 0.1 and 0.4 μg/ml, while the MICs of rifampicin were 0.1 and 0.2 μg/ml, respectively. The minimal bactericidal concentrations (MBCs) of isoniazid to the intracellular and extracellular H37Rv were 0.2 and 0.4 μg/ml, while the MCSs of rifampicin were 0.1 and 0.2 μg/ml, respectively. © 2006 Elsevier Ltd. All rights reserved.